2020
DOI: 10.1111/vox.12968
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with convalescent plasma as immunotherapy for COVID‐19 in China: Knowns and unknowns

Abstract: Background and objectives In the absence of a vaccine or specific drug treatment options for coronavirus disease (COVID-19), attention has been shifted in China to the possible therapeutic use of convalescent plasma. COVID-19 convalescent plasma (CCP) is currently under investigation. We summarized clinical studies and other research data available as of 5 May 2020 on CCP therapy according to the Clinical Treatment Guideline of COVID-19 Convalescent Plasma in China, as well as clinical experience at the First … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…A review about CP therapy [ 40 ] reported that convalescent plasma treatment appeared effective and safe for COVID-19, but there was clearly a need for well-designed RCTs to further evaluate its efficacy and safety. A randomized trial [ 34 ] declared only 2 adverse events existed among 52 individuals with treatment of CP.…”
Section: Discussionmentioning
confidence: 99%
“…A review about CP therapy [ 40 ] reported that convalescent plasma treatment appeared effective and safe for COVID-19, but there was clearly a need for well-designed RCTs to further evaluate its efficacy and safety. A randomized trial [ 34 ] declared only 2 adverse events existed among 52 individuals with treatment of CP.…”
Section: Discussionmentioning
confidence: 99%
“…However, most protocols require that patients should be convalescent for 2-4 weeks prior to donation, that only adults donate, that routine procedures for accepting blood and blood products donations be followed, and that plasma is tested to quantitatively assess the levels of antibodies (Chen and Xia, 2020;Tiberghien, 2020). Antibody titer thresholds are also not standardized but a titer of 1:160 of SARS-CoV-2 specific IgG is recommended (Chen and Xia, 2020). The Egyptian public health authorities are testing the effectiveness of convalescent plasma therapy for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these facts, we believe that hospitalized patients with COVID-19 should continue to be offered the potential benefit of CPT -which has been proven to save lives in other trials. [11][12][13][14][15] 1. CPT for COVID-19 has been shown in clinical trials to reduce mortality of up to 30-50% in seriously ill COVID-19 patients 2.…”
Section: Current Practical Recommendations For Cptmentioning
confidence: 99%